Trade openness, income, and role of institutions: A revisit using heterogeneous panel data models - Jayanthi Thennakoon; Jagath Dissanayake (Cogent Economics & Finance, 2015)
The positive association between trade openness and income has been debated over years due to serious estimation flaws prevailing in the cross-country empirical trade literature. The present paper contributes to this debate by re-examining the long-run relationship between trade openness and income per capita focusing on role of institutions. It does so by estimating a heterogeneous panel data model with 97 countries over the period 1980-2012 taking unobserved common factors into consideration. Our method is a more appropriate approach to estimate this relationship given the potential cross-section dependence and parameter heterogeneity associated with cross-country growth regressions. The results have found evidence to suggest that trade openness is positively and significantly associated with income per capita even after controlling for parameter heterogeneity, cross-section dependence and possible endogeneity. Results further suggest that better quality institutions complement the effects on income underscoring the significance of institutions in benefiting more from trade openness. This study provides more reliable estimates to support the claim that trade openness has significant and robust role on economic growth and development.
Keywords: F1; F43; C21; C23; 330; common factor models; cross-section dependence; international trade; economic growth of open economies